2015
DOI: 10.1177/1350650114568474
|View full text |Cite
|
Sign up to set email alerts
|

Variation of wear behavior of H13 steel sliding against different-hardness counterfaces

Abstract: Dry sliding tests for H13 steels sliding against different-hardness counterfaces were performed in air under a load of 50-300 N at 25-600 C on a pin-on-disk elevated temperature tester. The hardness of the counterface was noticed to appreciably affect the wear behavior of H13 steel. When H13 steel slid against a hard counterface (55 HRC), the wear rate increased with an increase of temperature. As the load increased, the wear rate marginally increased at 25 C and 200 C but rapidly increased at 400 C and 600 C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Studies have shown that (H disc /H pin ) was the key factor that affected the material wear characteristics. 20,28) However, the (H disc /H pin ) value was always above 1 at any temperature for the presented M2-38CrNi3MoV steel tribo-system. Therefore, it was no longer suitable to explain the wear behavior of 38CrNi3MoV steel using the (H disc /H pin ) value.…”
Section: Hot Hardness Of the Disc And Pinmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies have shown that (H disc /H pin ) was the key factor that affected the material wear characteristics. 20,28) However, the (H disc /H pin ) value was always above 1 at any temperature for the presented M2-38CrNi3MoV steel tribo-system. Therefore, it was no longer suitable to explain the wear behavior of 38CrNi3MoV steel using the (H disc /H pin ) value.…”
Section: Hot Hardness Of the Disc And Pinmentioning
confidence: 77%
“…16) The effect of the hardness of the material on the wear behavior was also studied, and it was found that the hardness ratio of the disc to the pin (H disc /H pin ) was the key factor affecting the material wear characteristics. 20) However, studies on the role of material matrix properties have been limited to the mechanical properties of materials at room temperature. There is still little research on the relationship between material properties and wear behavior at elevated temperatures, which must be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, friction-oxide layers would form on the worn surface and affect the state of the sliding pair. The friction-oxide layer is considered to be a decisive factor determining wear behavior, even wear mechanism [1][2][3][4][5][6][7][8][9][10][11][12][13][14][17][18][19]. In mild conditions [17][18][19], the formation and spalling of friction-oxide layers reach an equilibrium state; their existence indeed protects the worn surface from further wear.…”
Section: Wear Failure Mechanismmentioning
confidence: 99%
“…AISI H21 steel, is a typical tungsten-system hot-working die steel. The wear behavior and wear resistance of hot-working die steels were widely studied previously [1][2][3][4][5][6][7][8][9][10]. But the related researches for H21 steel was sparsely reported [3,6,8].…”
Section: Introductionmentioning
confidence: 99%